The Most Productive Faces Of Our World Of Thought - KARAGÖZ, Nail (Scientific Journal of Faculty of Theology, 2021)
Since the invention of writing, people have been making notes at the materials they have found and passing on their knowledge of the period in which they lived to the next generations. In Islamic thought, since the time of the Prophet (pbuh), scientific works have been written and the knowledge has been tried to be transferred to the next generations. In this context, there are authors who have produced a number of works that are surprisingly observed how they fit in a human life. In this study, we tried to identify such authors and the situations that enabled them to produce so many works. In this sense, we tried to give more space to Ahmet Rida Khan, Irec Efşar, Suyuti, Ibn Taymiyya, Ibn Tolun, Ihsan Ozanoglu which we consider to be prominent compared to the others. Each of these authors was able to produce astonishingly enough to fit into a human lifespan, and their knowledge and skills are at the top. It should be noted that each author we discussed produced works in numbers starting with seven hundred. In adition some of them wrote works on their own lives and works. Our study is based on literature review. We tried to reach the result by describing, grouping, comparing and evaluating the information we found in the literature.